The importance of retesting the hearing screening as an indicator of the real early hearing disorder - Silva, Daniela Polo Camargo da [UNESP]; Lopez, Priscila Suman [UNESP]; Ribeiro, Georgea Espíndola [UNESP]; Luna, Marcos Otávio de Mesquita [UNESP]; Lyra, João César [UNESP]; Montovani, Jair Cortez [UNESP] (Elsevier B. V., 2015)
Early diagnosis of hearing loss minimizes its impact on child development. We studied factors that influence the effectiveness of screening programs. To investigate the relationship between gender, weight at birth, gestational age, risk factors for hearing loss, venue for newborn hearing screening and pass and fail results in the retest. Prospective cohort study was carried out in a tertiary referral hospital. The screening was performed in 565 newborns through transient evoked otoacoustic emissions in three admission units before hospital discharge and retest in the outpatient clinic. Gender, weight at birth, gestational age, presence of risk indicators for hearing loss and venue for newborn hearing screening were considered. Full-term infants comprised 86% of the cases, preterm 14%, and risk factors for hearing loss were identified in 11%. Considering the 165 newborns retested, only the venue for screening, Intermediate Care Unit, was related to fail result in the retest. Gender, weight at birth, gestational age and presence of risk factors for hearing loss were not related to pass and/or fail results in the retest. The screening performed in intermediate care units increases the chance of continued fail result in the Transient Otoacoustic Evoked Emissions test.

O diagnóstico precoce da surdez minimiza impactos no desenvolvimento infantil. Fatores que interferem na efetividade dos programas de triagem são estudados. Verificar a relação entre sexo, peso ao nascimento, idade gestacional, presenc¸a de risco par deficiência auditiva, local de realização da triagem auditiva neonatal e resultados ‘‘passa’’ e ‘‘falha’’ no reteste. Estudo de corte prospectiva, em hospital de referência terciário. A triagem foi realizada em 565 neonatos, por meio das emissões otoacústicas evocadas transientes, em três unidades de internação antes da alta hospitalar e o reteste, no ambulatório. Sexo, peso ao nascimento, idade gestacional, presença de indicadores de risco para deficiência auditiva e local de realização do exame foram considerados. Nasceram a termo 86%, prematuros 14% e risco para deficiência auditiva, 11%. Dentre os 165 neonatos retestados, apenas o local de realização do exame, Unidade de Cuidados Intermediários, se relacionou com manutenção da ‘‘falha’’ no reteste. Sexo, peso ao nascimento, idade gestacional e presença de indicadores de risco para deficiência auditiva não se relacionaram com ‘‘passar’’ e/ou ‘‘falhar’’ no reteste. A realização do exame em unidades de cuidados intermediários aumenta a chance de permanência de ‘‘falha’’ no exame de Emissões Otoacústicas Evocadas Transientes.
A importância do reteste da triagem auditiva como indicador da real alteração auditiva precoce
Keywords: Hearing; Acoustic stimulation; Newborn; Neonatal screening; Audição; Estimulação acústica; Recém-nascido; Triagem neonatal